EFEKTIVITAS SISTEM INFORMASI DI DESA PURWOGONDO, KECAMATAN BOJA, KABUPATEN KENDAL - Annas Dwi Rahayu; Hesti Lestari; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The village has the authority to organize and take care of the interests of its people within the framework of the autonomy of the village itself. In order to answer various problems at the village level, the application of village e-government requires a careful planning. This underlies the initiative of the village-level government to run the Village Information System.Kendal Regency implemented the Village Information System since 2019, then regulated in Kendal Regent Regulation No. 39 of 2019 on Village Information System Development Guidelines as a follow-up to Central Java Governor Regulation No. 47 of 2016 on Village Information System Development Guidelines. This research aims to analyze the effectiveness of Information Systems in Purwogondo Village, Boja Subdistrict, Kendal Regency, as well as identify and analyze inhibition factors. This study uses a type of qualitative descriptive research with the determination of informants through purposive sampling techniques. Data collection techniques are used through observation, interviews, and documentation. The results of the study showed that based on seven phenomena of effectiveness of village information systems, namely relevance, variation of reports or outputs, and the quality of information can be said to be ineffective. This is due to the presence of obstacles in the application of Information Systems, (1) Human resources, namely the lack of ability to manage village information systems and the lack of regulation regarding job descriptions of each village information system management team at the village level, (2) Procedures, namely the absence of Operational Standard Procedures to provide quality information, and (3) Communication, namely the absence of communication or role built from the Village Head as a protector or from the Village Secretary as the managing chairman of Information System. The support from the Village Chief and the Village Secretary provided has not been felt by the village information system operator.